Implementasi Metode Teknologi Pembayaran Zakat Digital - Sugiyanto, Rama; Santi Singagerda, Faurani I (Jurnal Bisnis dan Ekonomi, 2024)
Indonesia, as one of the countries with the largest Muslim population in the world, has significant revenue potential from zakat payments to improve societal welfare. With the advent of the technology era, financial transactions have become more accessible through the emergence of Financial Technology. Among FinTech innovations, digital payments, particularly crowdfunding, are especially prominent in terms of zakat donations. This study explores the psychological dynamics underlying the adoption of digital zakat payment platforms, using the Theory of Planned Behavior, the Theory of Reasoned Action, and the Diffusion of Innovation Theory as the theoretical framework. Through a mixed-method approach, which includes empirical research and theoretical modeling, this study identifies barriers in the digital zakat payment process. The findings emphasize the importance of attitudes, subjective norms, and perceived behavioral control in shaping individuals' intentions to use e-zakat platforms. Furthermore, this study highlights the role of technological innovation in accelerating the adoption of digital zakat payments, contributing to increased efficiency and inclusivity in zakat management. Keywords: Zakat; TRA; TPB; Diffusion of Innovation